A Robust Approach to TDMA Synchronization in Aerial Networks - Pinto, Luis (2019)
Unmanned Aerial Vehicles (UAVs) can be a powerful tool for live (interactive) remote inspection of large-scale structures or areas of interest. Instead of manual, local, and labor-intensive inspections, we envision human operators working together with networks of semi-autonomous UAVs. The current state-of-the-art for low-delay high-throughput inter-vehicle networking relies on Time-Division Multiple Access (TDMA) techniques that require accurate synchronization among all network nodes. In this paper, we propose a delay-tolerant synchronization approach that converges to the correct order of the TDMA slots implemented over COTS WiFi in a fully-distributed way and without resorting to a global clock. This highly flexible solution allows building an ad-hoc aerial network based on a backbone of relaying UAVs. We show several alternatives to achieve this synchronization in a concrete aerial network and compare them in terms of slots’ overlap, throughput, and packet delivery. The results show that these alternatives lead to trade-offs in the referenced metrics. The results also provide insight into the delays caused by buffering in the protocol stack and especially in the WiFi interface.